BEL120: Consolidating Language Skills / Academy of Language Studies - UiTM, Academy of Language Studies (2012)
Read and analyse passages and articles on general topics, write grammatically correct sentences, write well-organised and coherent essays. Listen to and identify main ideas and supporting details communicate accurately, appropriately in social interactions and group discussions.